Evaluation of the Influence of Resistance Force Intensity on the Dynamic Behavior of a Millimeter-scale Vibro-impact Capsule Robot - Nguyen, Van-Du; Chu, Ngoc-Hung; Ngo, Quoc-Huy (Discontinuity, Nonlinearity, and Complexity, 2026)
The locomotion efficiency of capsule robots is highly sensitive to environmental resistance forces, especially in fluid-filled conditions. This study investigates a millimeter-scale vibro-impact capsule robot designed for gastrointestinal applications. Building on a validated dry friction model, we incorporate viscous drag and buoyancy to simulate realistic fluidic environments. A comprehensive physical and mathematical framework is developed to characterize the capsule's nonlinear dynamics. Numerical simulations and analytical tools, including time history analysis, phase trajectories, Poincaré maps, and bifurcation diagrams, are used to evaluate displacement efficiency across varying friction thresholds and fluid properties. Results show that high dry friction suppresses mobility, voltage decay reduces propulsion, and moderate fluid viscosity can enhance travel distance. These findings help identify optimal operating conditions for stable bidirectional motion and offer practical guidelines for the design and control of capsule robots in complex environments.